Causes and implications of bovine organs/offal condemnations in some abattoirs in Western Nigeria. (2009)
Food animals though sources of protein and revenue to man, also serve as vehicles of disease transmission. This work reviews a three year record of slaughtered cattle in 12 abattoirs/slaughter slabs in western Nigeria to determine the economic and public health issues associated with their disease conditions. Out of 641,224 cattle slaughtered, 51,196 (7.98%) were attributable to 14 diseases/conditions including tuberculosis, pneumonia, fascioliasis, pimply gut, paramphistomosis, cysticercosis, dermatophilosis, tonsillitis, taeniasis, ascariosis, abscess, mange, mastitis and immature fetuses. Pneumonia (21.38%), fascioliasis (20.28%) and tuberculosis (7.95%) were major reasons for condemnations; least being ascariosis (0.01%). The lungs (45.66%) and liver (32.94%) accounted for most organ condemned while the heart (0.02%) was the least affected. The proportions of pneumonia, fascioliasis and immature fetuses observed were not statistically different (Mean = 3895.7; 3654.0; 3467.3); however, asignificant difference existed with other conditions (MeanA = 3895.7; 3654.0; 3467.3; MeanB = 1359.7; 1057.7; 510.3). Organs/offal condemnations constituted loss of revenue and animal protein as 124,333 kilo kilogrammes worth of meat valued in Naira at N41,613,043 ($332,904) was lost over the period giving an average of N13,871,014 ($110,968) annually. This, coupledwith fetal wastage represented an economic loss; with associated public health implications.